Foxp3+ Regulatory and Conventional CD4+ T Cells Display Similarly High Frequencies of Alloantigen-Reactive Cells - Lalfer, Mélanie; Chappert, Pascal; Carpentier, Maxime; Urbain, Dominique; Davoust, Jean M.; Gross, David-Alexandre (Frontiers in Immunology, 2019)
Foxp3+ regulatory T cells (Tregs) play a major role in acquired immune tolerance to allogenic transplants. Their suppressive activity is thought to require T cell receptor (TCR)-driven antigen recognition; little, however, is known about the fraction of Tregs able to recognize alloantigens within this T cell subset primarily educated against self-antigens. Performing transfer experiments of Tregs or conventional T cells (Tconv) into both lymphoreplete and lymphopenic mice, we observed a similarly high proportion of cells signaling through their TCR and proliferating in allogenic hosts. Furthermore, using an in vivo proliferation assay with limited T cell numbers infused into lymphopenic mice, we found that the overall frequency of alloreactive Tregs was similar if not higher to that of alloreactive Tconv. Overall our study highlights a noticeably high level of alloreactive Foxp3+ regulatory T cells accounting for their predominant role in transplantation tolerance.